Controlled Growth of Large‐Sized and Phase‐Selectivity 2D GaTe Crystals. Issue 21 (19th April 2021) - Liu, Mingqiang; Yang, Shuo; Han, Mao; Feng, Simin; Wang, Gui‐Gen; Dang, Leyang; Zou, Bo; Cai, Yawei; Sun, Huarui; Yu, Jie; Han, Jie‐Cai; Liu, Zheng
Abstract: GaTe has recently attracted significant interest due to its direct bandgap and unique phase structure, which makes it a good candidate for optoelectronics. However, the controllable growth of large‐sized monolayer and few‐layer GaTe with tunable phase structures remains a great challenge. Here the controlled growth of large‐sized GaTe with high quality, chemical uniformity, and good reproducibility is achieved through liquid‐metal‐assisted chemical vapor deposition method. By using liquid Ga, the rapid growth of 2D GaTe flakes with high phase‐selectivity can be obtained due to its reduced reaction temperature. In addition, the method is used to synthesize many Ga‐based 2D materials and their alloys, showing good universality. Raman spectra suggest that the as‐grown GaTe own a relatively weak van der Waals interaction, where monoclinic GaTe displays highly‐anisotropic optical properties. Furthermore, a p‐n junction photodetector is fabricated using GaTe as a p‐type semiconductor and 2D MoSe2 as a typical n‐type semiconductor. The GaTe/MoSe2 heterostructure photodetector exhibits large photoresponsivity of 671.52 A W −1 and high photo‐detectivity of 1.48 × 10 10 Jones under illumination, owing to the enhanced light absorption and good quality of as‐grown GaTe. These results indicate that 2D GaTe is a promising candidate for electronic and photoelectronic devices. Abstract : A liquid‐metal‐assisted chemical vapor deposition method is proposed to achieve the controlled growth of large‐sized monolayer and few‐layer GaTe with high quality, high phase‐selectivity, chemical uniformity, and good reproducibility. The method can be extended to grow Ga‐based 2D materials and their alloys, including GaSe, GaS, GaTe1‐ x Se x, and even InSe, which significantly speed up the technological applications of 2D materials.